Molecular‐Iodine‐Catalyzed Transformation of Benzyl Amines to N‐Benzyl Benzamides via Oxidative Dehydrogenation/A2 like Self‐Coupling and Hydration under Metal‐Free Mild Conditions. Issue 12 (27th April 2017) - Saha, Arijit; Payra, Soumen; Banerjee, Subhash
Abstract: An efficient protocol for the transformation of benzyl amines to N ‐benzyl benzamides through oxidative dehydrogenation, A 2 like self coupling and hydration has been developed using mild I2 /TBHP catalytic system under metal‐free conditions . Abstract : A highly selective, efficient and mild protocol for the transformation of benzyl amines to N ‐benzyl benzamides has been developed using I2 /TBHP catalytic system via oxidative dehydrogenation/ A 2 like self coupling /hydration reaction sequences under metal‐free conditions.